Experimental Microbial Alteration and Fe Mobilization From Basaltic Rocks of the ICDP HSDP2 Drill Core, Hilo, Hawaii - Stranghoener, Marius; Schippers, Axel; Dultz, Stefan; Behrens, Harald (Frontiers in Microbiology, 2018)
The interaction of a single bacterial species (Burkholderia fungorum) with basaltic rocks from the ICDP HSDP2 drill core and synthetic basaltic glasses was investigated in batch laboratory experiments to better understand the role of microbial activity on rock alteration and Fe mobilization. Incubation experiments were performed with drill core basaltic rock samples to investigate differences in the solution chemistry during biotic and abiotic alteration. Additionally, colonization experiments with synthetic basaltic glasses of different Fe redox states and residual stresses were performed to evaluate their influence on microbial activity and surface attachment of cells. In biotic incubation experiments bacterial growth was observed and the release of Fe and other major elements from drill core basaltic rocks to solution exceeded that of abiotic controls only when the rock sample assay was nutrient depleted. The concentration of dissolved major elements in solution in biotic colonization experiments with synthetic basaltic glasses increased with increasing residual stress and Fe(II) content. Furthermore, the concentration of dissolved Fe and Al increased similarly in biotic colonization experiments indicating that their dissolution might be triggered by microbial activity. Surface morphology imaging by SEM revealed that cells on basaltic rocks in incubation experiments were most abundant on the glass and surfaces with high roughness and almost absent on minerals. In colonization experiments, basaltic glasses with residual stress and high Fe(II) content were intensely covered with a cellular biofilm. In contrast, glasses with high Fe(III) content and no residual stress were sparsely colonized. We therefore conclude that structurally bound Fe is most probably used by B. fungorum as a nutrient. Furthermore, we assume that microbial activity overall increased rock dissolution as soon as the environment becomes nutrient depleted. Our results show that besides compositional effects, other factors such as redox state and residual stress can control microbial alteration of basaltic glasses.